Sexual-perception processes in acquaintance-targeted sexual aggression - Treat, Teresa A. (Aggress Behav, 2018)
This study analyzes data from seven published studies to examine whether three performance-based indices of men's misperception of women's sexual interest (MSI), derived from a self-report questionnaire, are associated with sexual-aggression history, rape-supportive attitudes, sociosexuality, problem drinking, and self-reported MSI. Almost 2000 undergraduate men judged the justifiability of a man's increasingly unwanted advances toward a woman on the Heterosocial Perception Survey-Revised. Participants self-reported any sexual-aggression history, and some completed questionnaires assessing rape-supportive attitudes, sociosexuality, problem drinking, and self-reported MSI. A three-parameter logistic function was fitted to participants' justifiability ratings within a non-linear mixed-effects framework, which provided precise participant-specific estimates of three sexual-perception processes (baseline justifiability, bias, and sensitivity). Sexual-aggression history and rape-supportive attitudes predicted: (a) reduced sensitivity to women's affect; (b) more liberal biases, such that the woman's affect had to be more negative before justifiability ratings dropped substantially; and (c) greater baseline justifiability of continued advances after a positive response. Sexual-aggression history and attitudes correlated more strongly with sensitivity than baseline justifiability; remaining variables showed the opposite pattern. This work underscores the role of sexual-perception processes in sexual aggression and illustrates the derivation of performance-based estimates of sexual-perception processes from questionnaire responses.